2011
DOI: 10.3724/sp.j.1005.2011.00168
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of <I>Litopenaeus vannamei</I> TCP-1-eta gene and analysis on its relationship with cold tolerance

Abstract: To study the molecular mechanism of cold tolerance, we cloned TCP-1-eta homolog gene from Litopenaeus vannamei and studied its relationship with cold tolerance. Based on the sequence from electronic cloning, a pair of primers were designed, and a 1 705 bp cDNA was obtained by RT-PCR. The cDNA contains 1 629 bp ORF, which encodes a peptide of 542 aa. Tissue expression pattern by real-time PCR analysis revealed that TCP-1-eta mRNA mainly existed in muscle tissue. Cold induction by different temperatures revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…To study the molecular mechanism of cold tolerance, TCP-1-eta homolog gene cDNAwas obtained from Whiteleg shrimp Litopenaeus vannamei and was sequenced (Yin et al, 2011). TCP-1-eta gene expression depended on temperature.…”
Section: Stress Responsementioning
confidence: 99%
“…To study the molecular mechanism of cold tolerance, TCP-1-eta homolog gene cDNAwas obtained from Whiteleg shrimp Litopenaeus vannamei and was sequenced (Yin et al, 2011). TCP-1-eta gene expression depended on temperature.…”
Section: Stress Responsementioning
confidence: 99%
“…In L . vannamei , SNP 892C>T of Hsp70 was associated with resistance to Taura syndrome virus, and the level of cold tolerance was found to have an association with different genotypes of locus 731 in the ORF of TCP -1 -eta homolog gene (Zeng et al, 2008;Yin et al, 2011). Changes of the agglutinative activity against seven pathogenic bacteria were linked to mutations of three non-synonymous SNPs in the C-terminus of hemocyanin (Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, HSP upregulation had been associated with cold-tolerance in overwintering insects, antarctic notothenioid fish and Saccharomyces cerevisiae Parsell et al, 2013;Feder and Hofmann, 1999;Haslbeck and Vierling). While previous our lab showed that both HSP60 and four sHSPs were involved in cold tolerance in L. vannamei, the present study has implicated yet two more HSP proteins as participating in cold tolerance (Yin et al, 2011;Peng et al, 2013).…”
Section: Discussionmentioning
confidence: 52%